2022
DOI: 10.1155/2022/6481192
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin Inhibits Hepatic I/R-Induced Injury through Regulating PHB2/PINK1/Parkin Pathway

Abstract: Formononetin (FN), an isoflavone compound mainly isolated from soy and red clover, had showed its anti-inflammation, antioxidative effects in some degenerative diseases and cholestasis. However, the role of FN in protecting ischemia/reperfusion- (I/R-) induced liver injury and the possible mechanism were unclear. In this study, effects of FN on liver injury were investigated in a rat hepatic I/R model; further, mitophagy-related proteins were measured by immunoblotting or immunofluorescence. The possible roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…FMNT may reduce oxidative stress in liver disease, showing hepatoprotective potential. Mitochondrial dysfunction produces excess ROS, while FMNT promoted PHB2/PINK1/Parkin-mediated mitophagy pathway, reduced the production of ROS and then alleviated ischemia/reperfusion-induced liver injury (Ma et al, 2022). The H 2 O 2 molecule is a precursor of free radicals that can cause cell death (Halliwell, 1989).…”
Section: Ros Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…FMNT may reduce oxidative stress in liver disease, showing hepatoprotective potential. Mitochondrial dysfunction produces excess ROS, while FMNT promoted PHB2/PINK1/Parkin-mediated mitophagy pathway, reduced the production of ROS and then alleviated ischemia/reperfusion-induced liver injury (Ma et al, 2022). The H 2 O 2 molecule is a precursor of free radicals that can cause cell death (Halliwell, 1989).…”
Section: Ros Inactivationmentioning
confidence: 99%
“…Another study revealed that FMNT was able to elevate levels of SOD, CAT and GSH-Px in db/db mice, alleviating diabetic nephropathy (Lv et al, 2020). Studies of ischemia reperfusion showed apparent roles of FMNT in improving the activities of CAT, SOD and GSH-Px, and relieved damage of the cell membrane and increase in permeability evoked by superfluous oxygen-free radicals (Zhao et al, 2021;Ma et al, 2022). Except for ischemia-reperfusion, oxidative stress caused by overproduction of ROS and depletion of antioxidants in the defense system has also been implicated in the pathogenesis of acute myocardial infarction (AMI).…”
Section: Enzymatic Antioxidants Activationmentioning
confidence: 99%
“…Alcoholic extracts of lotus leaves, rich in flavonoids, have the potential to treat dyslipidemia in rats treated with LPV and RTV [155]. Third, the red clover isoflavones, formononetin, and biochanin A were shown to modulate NFκB/pAkt signaling molecules and protect against RTV-induced hepatotoxicity in in vivo animals [73,156,157]. Some flavonoids, such as quercetin, not only protect against drug-induced hepatotoxicity but are also effective as antiparasitic and anti-HIV/SARS-CoV-2 agents [158].…”
Section: Targeting Insulin Resistance Cellular Stress and Dyslipidemiamentioning
confidence: 99%